LIGHTWEIGHT DESIGN OF THE CUTTER HEAD OF THE PIPE JACKING MACHINE UNDER THE WEAKLY WEATHERED TUFF LAVA FORMATION (MT) - XU XianFeng; CHEN ZhouXiao; HUANG ZhiGang; XING PengFei (Jixie qiangdu)
In order to study the structure design and mechanical properties of the cutterhead of D2000 Slurry balanced pipe jacking machine for composite formation, the static analysis of the cutterhead model was carried out, and the equivalent stress and deformation nephogram of the cutterhead were obtained. It was determined that the dangerous position was located at the bottom of the front cutter installation side plate. The maximum equivalent stress value was 178.21 MPa, and the maximum deformation was 0.50 mm. The results showed that the cutterhead material was made of strength and stiffness requirements. Through the lightweight design of cutter head, the maximum stress, maximum deformation and cutter head mass are obtained. The results show that the stress and deformation of the improved cutterhead meet the optimization constraints. The mass reduction is reduced by 8.23% compared with that before optimization, which meets the requirements of lightweight design of cutterhead.